Diálogo, modernização e conflito: uma biografia do cardeal Dom Avelar Brandão Vilela - Zachariadhes, Grimaldo Carneiro (2017)
This thesis is a biography of Cardinal Don Avelar Brandão Vilela (b.1912 - d. 1986). This prelate stood out in the religious and political stages of Brazil and Latin America during middle and late 20th century. The archbishop was active during Brazilian Military Dictatorship (1964-1985). Even in this radicalization period, he managed to dialogue with many sections of society and Catholic Church, becoming a moderator of social and political conflicts. He also stimulated the changes that Catholic Church was passing through during 1950's; these changes were legitimated by Second Vatican Ecumenical Council (1962-1965). D. Avelar was an important Latin American moderniser bishop and presided the Conference of Latin American Bishops, held in 1968, that marked Latin American Catholic Church history